Implementasi 2D Barcode pada Label Pangan Olahan Sebagai Kekuatan Pengawasan Badan Pengawas Obat dan Makanan - Dessy Setiawanti (LPPM Universitas Terbuka, 2021)
Currently, the distribution of processed food products is required to fulfill the regulations on the safety, quality, and nutrition of the food product. One of the three elements that was applied to processed food is in the form of food labels. Information on food labels aims to explain that the information listed is correct, it is not easily damaged and come off, is easy to see and read through the Distribution Permit Number (NIE). BPOM has a strong synergy in food product supervision by issuing the implementation of 2D barcodes on food labels as a policy to reduce the risk of circulation of counterfeit or illegal food products. The method used in this work is a literature study through data collection based on applicable laws and regulations as well as reporting on food label control. The intensification of food product supervision carried out by BPOM at retail and distribution facilities found many unauthorized (TIE) products, expired products, and damaged products. The results of the data obtained on the findings of the supervision of food products were mostly found in TIE products with the percentage of findings for TIE products at Retail Facilities by 52%, while the percentage of findings for TIE products in Importer/Distributor Warehouses were 72%. With the latest technology, the issuance of 2D Barcode implementations on processed food labels has a large positive impact on stakeholders, including the government, the food industry, and society. The application of 2D Barcode strive to be able to build people's knowledge to be more responsive and intelligent in processing information in the future.